Effect of Deep Relaxation on Heart Rate Variability in Sedentary Females - Fatema, Monzur E; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2015)
Background: Lower heart rate variability (HRV) in sedentary people is associated with higher risk of coronary heart diseases. Deep Relaxation Technique (DRT) generate higher HRV which reduces the risk of coronary heart disease. Objective: To assess HRV after practicing DRT to find out its effect on cardiac autonomic nerve function in sedentary subjects. Methods: This study with intervention by DRT was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University from July 2012 to June 2013 on 30 apparently healthy sedentary females aged 25-35 years practicing DRT for 3 months. 30 apparently healthy sedentary females who had no experience of relaxation technique constituted control. All subjects were sedentary housewives. The study subjects were participants in a private yoga center in Dhaka. HRV was assessed by RMS polynte D and frequency domain parameters were analysed. Statistical analysis was done by Independent Sample t-test. Results: Total power (p<0.001), HF power (p<0.01), HF norm (p<0.05) were significantly higher and LF power (p<0.001), LF norm (p<0.05), LF/HF (p<0.01) were significantly lower in the relaxation group than those of non relaxation group. Conclusion: Cardiac autonomic nerve function was improved by practice of DRT with parasympathetic dominance in sedentary females. DOI: http://dx.doi.org/10.3329/jbsp.v9i1.22787 Bangladesh Soc Physiol. 2014, June; 9(1): 6-10